(untitled) (Bangladesh Journal of Psychiatry, 2017)
Standard scale to assess the symptoms of depression, anxiety and stress among MBBS students are essential to take necessary steps to treat or prevent any psychiatric morbidity. But there was no such convenient tool in Bangla to measure the stated symptoms. With an objective to obtain a convenient scale to measure severity of above symptoms, short version of Depression Anxiety Stress Scales (DASS 21) was translated into Bangla and the study was carried out to validate this Bangla version with permission from the author of the original instrument. Two translations and back translations were carried out. A harmonized version was produced after meetings by persons involved in translation process in meetings. After pretesting on ten students and reviewing by panel of experts, finalized Bangla version of DASS 21 (DASS 21 -BV) was obtained. A cross sectional study was carried out among MBBS students of Pabna Medical College, Pabna using purposive sampling technique to validate this scale. They were given both Bangla and English version of the scale 3 to 7 days apart. Analysis was done on 15 samples. Correlation for depression subscale was 0.976, anxiety subscale was 0.917 and stress subscale was 0.931. Correlation was significant at the 0.01 level (2-tailed). Cronbachs Alpha for Depression, Anxiety and Stress subscales were 0.987, 0.957, 0.964 respectively. This Validated Bangla version of DASS 21 can be used to measure severity of depression among medical students and persons having similar academic background treatable. Bang J Psychiatry Dec 2014; 28(2): 67-70